2003
DOI: 10.1080/0307945031000154071
|View full text |Cite
|
Sign up to set email alerts
|

Association between in vitro heterophil function and the feathering gene in commercial broiler chickens

Abstract: We recently showed that in vitro heterophil functional efficiency in commercial broiler chickens is genetically controlled and may be a sex-associated trait. To further characterize the genetic mechanism(s) of heterophil functional efficiency, we wanted to determine whether the feathering gene, present on the Z sex chromosome, contributes to heterophil functional efficiency. Heterophils from two pairs of broiler lines were evaluated; each pair contained a fast feather (FF) (lines A and X) and a slow feather (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 23 publications
2
24
1
2
Order By: Relevance
“…There are also reports where avian PMN respond differently compared with the mammalian PMN. Human neutrophil killing is enhanced following an increase in JNK activation (Yeh et al, 2010); however, this is not what was observed in the present study where heterophils from line B chickens had elevated levels of JNK, yet their ability to kill SE is reduced compared with line A (Swaggerty et al, 2003a). The Yeh et al study utilized opsonized bacteria while the SE in the current study was non-opsonized; however, this is not likely to be the reason for the differences as opsonized SE produces similar activation of JNK to that which was presented herein (Swaggerty, unpublished data).…”
Section: Discussioncontrasting
confidence: 54%
“…There are also reports where avian PMN respond differently compared with the mammalian PMN. Human neutrophil killing is enhanced following an increase in JNK activation (Yeh et al, 2010); however, this is not what was observed in the present study where heterophils from line B chickens had elevated levels of JNK, yet their ability to kill SE is reduced compared with line A (Swaggerty et al, 2003a). The Yeh et al study utilized opsonized bacteria while the SE in the current study was non-opsonized; however, this is not likely to be the reason for the differences as opsonized SE produces similar activation of JNK to that which was presented herein (Swaggerty, unpublished data).…”
Section: Discussioncontrasting
confidence: 54%
“…Swaggerty et al (25) compararon la actividad fagocítica y bactericida de heterófilos de pollos de emplume rápido y emplume lento. Los autores demostraron que los pollos de emplume rápido presentaron mayor índice fagocítico y mayor actividad bactericida.…”
Section: Discussionunclassified
“…Swaggerty et al (25) compared the phagocytic and bactericidal activity of chicken heterophiles in fast and slow feathering. The authors demonstrated that fastfeathering chickens showed a higher phagocytic Los resultados evidenciados en este trabajo sobre la aglutinación bacteriana, permiten inferir que la suplementación con SH al 0.1 y 0.2% mejoran el efecto de la aglutinación bacteriana en el suero de gallinas ponedoras (p<0.05); Aunque no se encontraron datos publicados en esta especie para realizar comparaciones, estos resultados tienen relación con los presentados por Behera et al (18) quienes realizaron una inmunización parenteral con ácido glicólico en Rohita labeo reportando que el grupo tratado mostró una diferencia significativamente mayor en la prueba de aglutinación bacteriana el primer día de inmunización sin obtener diferencia significativa a los 21 y 42, datos que difieren de los resultados presentados en este trabajo puesto que la suplementación con SH mejoró significativamente la aglutinación bacteriana en todos los muestreos (día 8, 30 y 60).…”
Section: Discussionunclassified
“…To our knowledge and with the exception of our initial report (Swaggerty et al , 2003a), there are no studies evaluating the role of the feathering gene in either innate immune responsiveness or heterophil function in chickens. Therefore, our results showing that the bactericidal killing mechanisms of degranulation and oxidative burst were linked to the recessive k fast feathering gene were the first report to show direct linkage between the feathering gene and innate immunity in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…The initial studies by our group, as well as all subsequent evaluations, have shown a dichotomy of innate immune responsiveness between fast and slow feathering lines at the parent level and F1 generations. In all immunologic evaluations of the lines of these chickens, fast-feathering chickens have a more effective heterophil-mediated innate immune response with increased resistance to bacterial challenges compared with their slow-feathering counterparts (Swaggerty et al , 2003a(Swaggerty et al , ,b, 2004(Swaggerty et al , , 2005a(Swaggerty et al , ,b, 2006Ferro et al , 2004). The objective of the present study was to determine whether the feathering gene was actually linked to, not just associated with, increased in vitro heterophil function, the cytokine/chemokine mRNA expression levels produced by heterophils, or increased resistance to in vivo liver/spleen organ invasion by S. enteritidis.…”
Section: Discussionmentioning
confidence: 99%